An experimental evaluation of thermophysical properties of colloidal suspension of carbon-rich fly ash microparticles and single-walled carbon nanotubes in Jet-A fuel and its impact on evaporation and burning rate - Ahmed Aboalhamayie; Nadeem Ahmad; Yang Zhang; Mohsen Ghamari; Numan Salah; Jameel Alshahrani (Fuel Processing Technology)
This study presents an experimental evaluation of the thermophysical properties of colloidal suspensions of carbon-rich fly ash microparticles (CFA) and single-walled carbon nanotubes (SWCNT) in Jet-A fuel, focusing on their impact on evaporation and burning rates. The research explores the effects of these carbon-based additives on key parameters such as thermal conductivity, viscosity, surface tension, evaporation rate, and combustion behavior. Utilizing a hybrid preparation method combining sonication and surfactants, stable colloidal suspensions were prepared for experimental analysis. The results demonstrate that both CFA and SWCNT enhance the thermal conductivity of Jet-A fuel, with SWCNT achieving a notable 13 % increase at a 1 wt% concentration, while CFA achieves an 8 % increase at a 3 wt% concentration. The study also reveals distinct trends in viscosity and surface tension, with SWCNT causing a significant non-linear increase in viscosity compared to CFA. In combustion experiments, the evaporation rates of CFA and SWCNT suspensions showed considerable improvement, with CFA demonstrating up to an 87 % increase at 1 wt% concentration. The study concludes with an analysis of ignition delay, highlighting the superior performance of SWCNT in reducing ignition time due to their high thermal conductivity and the presence of iron nanoparticles on their surface.